Solar Light-Assisted C–H Activation and C–C Coupling of Hindered N,N-Dimethyl-Anilines with Activated Methylene Compounds - Santra, Sourav Kumar; Rahamim, Jonatan; Dorfman, Ortal; Kashid, Abhijit; Parvari, Galit; Eichen, Yoav; Szpilman, Alex M. (Synthesis, 2025)
This article describes the use of dimethyl-aniline-alkyl halide charge transfer complexes as a linchpin for sunlight-initiated C–C bond formation with activated methylene compounds, including malonates, malononitriles, and 2-cyano-esters. DFT calculations shed light on charge transfer complex formation and structure as well as on the mechanism.
Keywords: Sunlight; Visible light; Charge-transfer complex; Electron donor–acceptor complex; C–C bond formation